Kompresi Data Menggunakan Algoritme Huffman - Julio Adisantoso; Danny Dimas Sulistio; Bib Paruhum Silalahi (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2004)
Text compression algorithms are normally defined in terms of a source alphabet of 8-bit ASCII codes. Huffman algorithm is the most popular methods of text compression. Thisresearch used static and adaptif Huffman algorithms to compress text data, and also compareit. Variation of character occurs will decrease compression ratio. Iteration time of staticHuffman algorithm for compress and decompress is faster than adaptif Huffman algorithm,but performance of adaptif Huffman algorithm is best.Keywords: text compression, static and adaptif huffman algorithm.